The Role of Municipalities in Environmental Management: a Case Study of Rzgów Municipality - Olejnik, Dorota; Cieplucha, Paula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Managing the environment in a sustainable manner allows for economic, social, and cultural development. The task of the municipality is to meet the basic needs of residents. The article presents the method of environmental management in the Rzgów Municipality and preventive actions in the form of monitoring, which are used to constantly control individual elements of the environment. Based on the collected data, a SWOT analysis was created along with an indication of possible actions and activities aimed at improving the conditions of the natural environment.
Keywords: environmental management; SWOT analysis; environmental monitoring; Rzgów Municipality